Shoetok Online Shoe Store Application Design to Increase Shoe Sales - Nugroho, Lucky Setyo; Ina Sholihah Widiati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The design of the ShoeStok application was carried out using the Design thinking research method to increase shoe sales. This application is designed with an intuitive user interface and provides various payment options, stock checking features, product availability notifications, as well as reviews and ratings of products that have been purchased. Design thinking is used to find the best solution for the problem at hand, with the stages of understanding, ideation, prototyping, and testing. Wireframing, prototyping, and user testing techniques are used to determine the layout and elements that will be displayed in the application. The result of designing this application is a Shoestok e-commerce application which has an intuitive UI and is easy for customers to use, which is expected to help increase shoe sales.